The Upper Jurassic (Kimmeridgian) fluvial-aeolian systems of the southern Neuquén Basin, Argentina - Veiga, Gonzalo Diego (2007)
The Kimmeridgian Quebrada del Sapo Formation in the southernmost Neuquén Basin in Argentina represents a succession up to 40 m thick of coarse- to fine-grained fluvial deposits overlain by aeolian deposits. These fluvial-aeolian deposits reflect a significant palaeogeographic change in the basin and are related to a major, tectonically enhanced, relative sea-level fall. The fluvial section is dominated by braided-channel, fine-grained ephemeral, and sheetflood deposits. Aeolian facies are dominated by dune deposits, with minor sandsheet and interdune units. Changes in the nature of both fluvial and aeolian sedimentation within the studied area suggest a regional variability of accommodation/sediment supply conditions. The regional changes of the aeolian succession likely reflect different relative positions within a major erg. In the upwind margin of the erg, a shallow water table promoted water-lain sedimentation in interdune areas, whereas in the central parts of the erg, dry sediment accumulation took place above the regional water-table level. The vertical transition observed in the Quebrada del Sapo Formation, from fluvial to aeolian deposits, may be the result of a local climatic change to drier conditions due to the development of a climatic barrier imposed by growth of a magmatic arc to the west. Alternatively, the vertical transition could be related to a lowering of the water table associated with the compartmentalization of the basin during a period of low sea level. © 2006 International Association for Gondwana Research.